2008
DOI: 10.1093/rpd/ncn037
|View full text |Cite
|
Sign up to set email alerts
|

European survey of dental X-ray equipment

Abstract: The implementation of an X-ray Quality Assurance (QA) program is a legal requirement in Europe as stipulated in the EU Council Directive 97/43/EURATOM (MED). A review of the literature has identified that European countries are performing some level of QA testing of their dental X-ray equipment, although the type and level to which testing is performed can differ. The European SENTINEL co-ordination action proposed to collate a survey of equipment data for both conventional and digital dental X-ray installatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
3
8
0
1
Order By: Relevance
“…Similar findings have been reported previously both in the United Kingdom (Tugnait et al. 2003) and mainland Europe (Gallager et al. 2008).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similar findings have been reported previously both in the United Kingdom (Tugnait et al. 2003) and mainland Europe (Gallager et al. 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the present study recorded that the use of rectangular collimation was more prevalent amongst younger practitioners. In continental Europe, a recent study (Gallager et al. 2008) found that circular collimators appear to be the routine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Die Notwendigkeit der systematischen Einarbeitung von Mitarbeitern und der Kenntnisstand aller Beteiligten an der Anfertigung eines Röntgenbildes ist somit ein entscheidendes Qualitätsmerkmal (Geibel 2010). In einer Veröffentli-chung zur europäischen Röntgenausstattung wird auch darauf aufmerksam gemacht, dass Schulungen und Fortbildungen unerlässlich im Umgang mit den Geräten und des Equipments sind (Gallagher et al 2008).…”
Section: Diskussionunclassified